Blood Perfusion and Cellular Microstructural Changes Associated With Iron Deposition in Multiple Sclerosis Lesions - Sheng, Huaqiang; Zhao, Bin; Ge, Yulin (Frontiers in Neurology, 2019)
ABSTRACT: Background and Purpose: Susceptibility-weighted imaging (SWI) has been emerged as a useful clinical tool in many neurological diseases including multiple sclerosis (MS). This study is to investigate the relationship between SWI signal changes including due to iron deposition in MS lesions and tissue blood perfusion and microstructural abnormalities to better understand their underlying histopathologies. Methods: Forty-six patients with relapsing remitting MS were recruited for this study. Conventional FLAIR, pre- and post-contrast T1-weighted imaging, SWI, diffusion tensor imaging (DTI), and dynamic susceptibility contrast (DSC) perfusion MRI were performed in these patients at 3T. The SWI was processed using both magnitude and phase information with one slice minimal intensity projection (mIP) and phase multiplication factor of 4. MS lesions were classified into 3 three groups based on their lesional signal appearance on SWI mIP relative to perilesional normal appearing white matter (peri-NAWM): Type-1: hypointense, Type-2: isointense, and Type-3: hyperintense lesions. The DTI and DSC MRI data were processed offline to generate DTI-derived mean diffusivity (MD) and fractional anisotropy (FA) maps as well as DSC-derived cerebral blood flow (CBF) and cerebral blood volume (CBV) maps. Comparisons of diffusion and perfusion measurements between lesions and peri-NAWM as well between different types of lesions were performed. Results: A total of 137 lesions were identified on FLAIR in these patients that include 40 Type-1, 46 Type-2, and 51 Type-3 lesions according to their SWI signal. All lesion types showed significant higher MD and lower FA compared to their peri-NAWM (P<0.0001). Compared to Type-1 lesions (likely represent iron deposition), Type-2 lesions had significantly higher MD and lower FA (P<0.001) as well as lower perfusion measurements (P < 0.05), while Type 3 lesions had significantly higher perfusion (P<0.001) and lower FA (P < 0.05). Compared to Type-2, Type-3 lesions had higher perfusion (P < 0.0001) and marginally higher MD and lower FA (P<0.05). Conclusion: The significant differences of diffusion and perfusion MRI metrics associated with MS lesions that appear with different signal appearance on SWI may help to identify the underlying destructive pathways of myelin and axons and their evolution related to inflammatory activities.